2007
DOI: 10.1379/csc-222r.1
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic chaperone-like RNA induces congophilic aggregates and facilitates neurodegeneration in Drosophila

Abstract: Protein aggregation is a hallmark of many neurodegenerative diseases. RNA chaperones have been suggested to play a role in protein misfolding and aggregation. Noncoding, highly structured RNA recently has been demonstrated to facilitate transformation of recombinant and cellular prion protein into proteinase K-resistant, congophilic, insoluble aggregates and to generate cytotoxic oligomers in vitro. Transgenic Drosophila melanogaster strains were developed to express highly structured RNA under control of a he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…In addition, the putative function of the largest rRNA in prion formation/propagation provides mechanistic support for previously unexplained observations in yeast showing the ability of 3 µm plasmid (encoding rRNA) to induce [ psi − ] to [ PSI + ] conversion when introduced into a [ psi − ] strain [46] . Very recently, it has been shown that in Drosophila melanogaster , overexpression of chaperone-like highly structured RNA induces congophilic aggregates and facilitates neurodegeneration [47] , also suggesting that a highly structured RNA alone could be able to trigger neurodegeneration through chaperone-like facilitation of protein misfolding and aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the putative function of the largest rRNA in prion formation/propagation provides mechanistic support for previously unexplained observations in yeast showing the ability of 3 µm plasmid (encoding rRNA) to induce [ psi − ] to [ PSI + ] conversion when introduced into a [ psi − ] strain [46] . Very recently, it has been shown that in Drosophila melanogaster , overexpression of chaperone-like highly structured RNA induces congophilic aggregates and facilitates neurodegeneration [47] , also suggesting that a highly structured RNA alone could be able to trigger neurodegeneration through chaperone-like facilitation of protein misfolding and aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…In the latter case, memory was retained for up to 8 h because retrieval of the memory trace is facilitated by the presentation of a fertilized female to the male (Kamyshev et al 1999). The CCSP is used widely for evaluation of basic courtship behavior and learning ability and memory retention in Drosophila (Kuzin et al 2014;Savvateeva-Popova et al 2007;Savvateeva-Popova et al 2008;Godenschwege et al 2004;Redt-Clouet et al 2012;Savvateeva et al 2000;Fedotov et al 2020).…”
Section: Learning and Short-term Memorymentioning
confidence: 99%
“…However, genetic chaperonopathies have a fairly early onset, while acquired chaperonopathies become exposed in the elderly, occasionally in association with other diseases. It has also been revealed that few prominent groups of chaperone are represented by the 'chaperonopathies by mistake' in which a molecular chaperone may be normal, although takes part in a cascade which indulges disease progression rather than the disease reversal [47]. In such condition, the pathology can be manifested by two types of pathogenic cascades; first the pathway is usual and comprises the participation of one or more chaperones which develops into part of a morbid process; and second the cascade that includes chaperones is not part of a physiological process within the cell, although comes to be potent and functional in morbid cases.…”
Section: An Interlink Between Chaperoning Machinery and Chaperonopathiesmentioning
confidence: 99%